Healthcare information technology (IT) and management systems Part 2 – national experiences - Wdowiak, Leszek; Kamiński, Zygmunt; Horoch, Andrzej; Bojar, Iwona (Polish Journal of Public Health, 2009)
Transformation of organizational model of Healthcare system into uniform, integrated and fl exible structure by implementing IT system is benefi cial for patients’ safety as well as the rationalization of activities in health protection system. The benefi ts of the system implementation koncern both meeting of patients and providers’ needs and improve the process of taking decision by the participants of health protection system.The aim of the research is to analyse the past and prezent experiences related to the implementation of IT system in Poland. Subsequent stages of launching of individual IT systems have been presented: RUM II aiming at pilot implementation of e-prescription system, START – aiming at implementing the Medical Services Register in Silesia Region and also currently implemented and improved National System of Health Protection.The national project of the implemented IT health protection system is a comprehensive venture including features not present as a whole in any of the foreign projects. Introducing of IT systems suggests the need for dividing its realization into stages. For getting the best possible effects the implementation of individual stages should be effi cient and consistent. There are necessary changes in legislation as well as the conviction of the policy-makers about the need for such solutions.